Doing business in Guyana : Guyana's investment guide 2006 (The Office GeorgetownGY, 2006)
Presents background information on the country and looks at the economy and government priorities. Highlights areas of opportunity and notes the operating environment
Keywords: INVESTMENT PROMOTION